SPATIAL PATTERNS AND WELLNESS IMPACTS OF LPG STATIONS IN EGOR LGA, NIGERIA - Egharevba, Jolly Osaretin (African Journal of Social and Behavioural Sciences, 2025)
This study investigates the spatial distribution of Liquefied Petroleum Gas (LPG) stations in Egor Local Government Area (LGA) and examines their perceived implications on residents’ health and well-being. A multi-stage sampling design was employed. Buffers of 100m, 200m, 300m, 400m, and 500m were created around each LPG station, and 100m, 200m, and 300m buffers were made around each LPG retail shop. Residential buildings within these buffers were identified, numbered, and randomly selected using a table of random numbers. A questionnaire was administered to one adult resident in each selected building, resulting in a total of 325 questionnaires, which constituted the study’s sample size. By analysing spatial patterns, the research identifies areas of high concentration of LPG facilities and assesses the environmental stressors related to their presence. Residents’ perceptions, including anxiety, sleep disturbances, and feelings of helplessness to change location, are explored to understand how proximity to LPG outlets impacts their psychological and physical wellness. This study uniquely combines geospatial analysis with psychological assessments to examine the impact of LPG proximity on well-being within the context of rapid urbanisation in Nigeria. The findings reveal significant links between the location of LPG stations and increased anxiety and sleep disturbance levels among residents, particularly in areas with higher concentrations of LPG outlets. These insights contribute to urban planning by highlighting the need for stricter regulations and safety measures to mitigate the negative impacts of LPG stations on residential areas, offering valuable information for policymakers and stakeholders in community health and urban facility management.